Peran Kolonel Maludin Simbolon Sebagai Panglima Sub Teritorium Sumatera Selatan (Subkoss) di Lubuklinggau Tahun 1947-1948 - Berlian Susetyo; Ravico Ravico (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2021)
Abstract: SUBKOSS was formed on May 17, 1946 as a result of the Republic of Indonesia Army Conference (TRI) in Bukit Tinggi which was led by the Commander of the Sumatra Command, Mayjend Suhardjo Hardjowardoyo. However, the determination to start the SUBKOSS was retroactive starting January 1, 1946. Then the city of Lubuklinggau was one of the areas that became the military seat of SUBKOSS during the Second Dutch Military Aggression led by Colonel Maludin Simbolon. This study uses a historical research method with the following steps: heuristics, source criticism, interpretation, and historiography. The results showed that Colonel Maludin Simbolon had attended Gyugun military education in Pagaralam in 1943 during the Japanese occupation, then he was appointed commander of the third South Sumatra Sub-Command, then during the Dutch Military Aggression II issued a policy of "Beleid Operation Commander of the South Sumatra Sub Territory" , henceforth to become guidelines and guidelines for all Indonesian National Armed Forces in the South Sumatra Sub-Territory.Keywords: Maludin Simbolon, SUBKOSS, Dutch Military Aggression II.